Efecto sinérgico de la aplicación de biofertilizante y fertilizante nitrogenado en pasturas - Francisco Adolfo Gutiérrez-León; Soraya Patricia Alvarado-Ochoa; Jaime Fabrizzio Reascos-Castillo; Evelyn Nicole Ortiz-Flores; Arnulfo Rigoberto Portilla-Narvaez; Marco Antonio Rivera-Montesdeoca (Pastos y Forrajes, 2023)
Objective: To evaluate the synergistic application of biofertilizer and water-soluble fertilizer on the yield and quality of pastures under the soil and climate conditions of Tumbaco-Ecuador.